Modality distance between graphs - Kraetzl M.; Wallis W.D. (Utilitas Mathematica, 2006)
In this paper an application of tournament matrices and sequences of strength vectors to analysis of communication networks is given. Snapshot matrices of individual members of time series of weighted digraphs are defined and used for the implementation of a generalization of tournament scoring. A measure called the modality of a node is defined; modality distance between snapshots is then defined and used to measure distance between consecutive members of the time series of digraphs.